The effect of covid-19 on bank proftability: Evidence of m-banking and e-banking in Indonesia - Anggraeni Anggraeni; Basuki Basuki; Rahmat Setiawan (Universitas Hayam Wuruk Perbanas, 2022)
Covid-19 affected the banks’ financial acitivities globally and, therefore, mobile banking can become solution for doing a distancing transaction. This study tries to observe if mobile transaction has significant effect of income in private and public bank in Indonesia. This study collects the data about bank profitability and the number of mobile banking users before and during Covid-19 pandemic from BCA and BNI in Indonesia. The data of mobile transaction is divided into three, mobile, internet, and SMS banking. The data of income divided into two, premium/net and operational income. The data is analyzed using linear regression method to observe if mobile transaction has effect toward income variables. The data is analyzed using SPSS. The result showed that before pandemic, those three mobile transaction have strong correlation toward the increasing number of net and total operational income in BNI. In BCA, mobile banking has a significant effect on net and total operational income. During pandemic, mobile transactions have negative correlation toward net income, while operational income has positive one for BNI, but negative for BCA. It can be concluded that internet, mobile, and SMS banking have correlation toward net and total operational income.